2021
DOI: 10.21037/tlcr-21-156
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of peripheral blood biomarkers with clinical outcomes in NSCLC patients with high PD-L1 expression treated with pembrolizumab

Abstract: Background: Immune checkpoint inhibitors (ICIs) are currently the standard therapy in advanced nonsmall cell lung cancer (NSCLC); however, there is no well-established prognostic biomarker. We investigated the relationship between survival outcomes and three peripheral blood biomarkers, including the neutrophilto-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and monocyte-to-lymphocyte ratio (MLR), as well as a new score termed the risk blood biomarker (RBB), calculated from the combination of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Recently, an increasing number of studies have focused on the use of hematological markers to assess the efficacy of immunotherapy in tumor patients. Studies have shown that using markers such as NLR, SII and LDH to identify patients with poor immunotherapy is a potential approach (59,60). Therefore, we explored whether HPSS, which integrates multiple hematological markers, is equally valuable in predicting immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of studies have focused on the use of hematological markers to assess the efficacy of immunotherapy in tumor patients. Studies have shown that using markers such as NLR, SII and LDH to identify patients with poor immunotherapy is a potential approach (59,60). Therefore, we explored whether HPSS, which integrates multiple hematological markers, is equally valuable in predicting immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 72 Other studies constructed risk blood biomarkers by combining white blood cell count and NLR. 73 Meanwhile, high eosinophil count (⩾1.5%) and relative lymphocyte count (⩾17.5%) were proved to be independent baseline characteristics associated with longer OS in melanoma patients treated with pembrolizumab. 74 Kiriu et al 75 found that patients with PsP have significantly lower NLR than patients with true tumor progression before and after treatment.…”
Section: Peripheral Blood Biomarkersmentioning
confidence: 91%
“…It has been reported that IFN-γ–related gene expression signatures constructed with 10 genes or 28 genes are able to predict the response to pembrolizumab in patients with metastatic melanoma [ 179 ]. In the CheckMate 275 and KEYNOTE-028 trials, higher scores of the 25-gene or 6-gene IFN-γ signature were demonstrated to be associated with a better immunotherapy response in urothelial and esophageal carcinomas [ 19 , 180 ]. The exploratory analyses from the POPLAR trial revealed that high T-effector-IFN-γ–associated gene expression predicted an OS benefit from atezolizumab over docetaxel, whereas in patients with low T-effector-IFN-γ–associated gene expression, there was no significant difference in OS between those treated with atezolizumab or docetaxel [ 35 ].…”
Section: Tumor Microenvironment (Tme)-based Biomarkersmentioning
confidence: 99%
“…High relative eosinophil counts (≥1.5%) and relative lymphocyte counts (≥17.5%) were demonstrated to be independent baseline characteristics that were correlated with longer OS in melanoma patients treated with pembrolizumab [ 121 ]. A new score, termed the risk blood biomarker, is calculated by combining the white blood cell count and neutrophil-monocyte-to-lymphocyte ratio, and was associated with a better survival and response to immunotherapy [ 180 ]. Elevated pretreatment neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio were independently associated with poorer OS and PFS and lower response rates in NSCLC patients treated with nivolumab [ 122 ].…”
Section: Tumor Microenvironment (Tme)-based Biomarkersmentioning
confidence: 99%